SEROTYPE-SPECIFIC AND HAEMADSORPTION PROTEIN OF THE AFRICAN SWINE FEVER VIRUS - Alexey D. Sereda; Anna S. Kazakova; Ilnaz R. Imatdinov; Denis V. Kolbasov (Slovenian Veterinary Research, 2018)
This review presents comparative results of simultaneously conducted studies on proteins responsible for the haemadsorption and serotype-specific properties of African swine fever virus (ASFV). An ASFV gene EP402R (or LMW8-DR) encoding protein CD2v homologous to murine, human or porcine T-cell adhesive receptor was found. The CD2v was shown to be directly involved into a haemadsorption process, and expressed in ASFV-infected cells as a glycoprotein with a molecular weight of approximately 105-110 kDa. In the presence of a glycosylation inhibitor, tunicamycin, its molecular weight is about 42 kDa. In ASFV-infected cells labeled with 3H-glucosamine or 14C-sodium acetate, a virus-specific major glycoprotein with a molecular weight of 110-140 kDa (gp 110-140) was identified using radioimmunoprecipitation assay. Using ASFV reference strains belonging to seroimmunotypes I-IV and the corresponding antisera active in haemadsorption inhibition assay (HADIA), we determined that gp 110-140 defines the serotype specificity. Genotyping on the basis of the genetic locus encoding the CD2v and a C-type lectin protein also showed a concurrence with the grouping of ASFV isolates and strains based on their seroimmunotypes. Immunization of pigs with the gp 110-140 within liposomes, or a recombinant haemagglutinin (CD2v) protected 67 to 100% of animals from death due to their subsequent infection with homologous virulent ASFV strains. Based on the physico-chemical and biological characteristics of the gp 110-140 and CD2v it is suggested that they are one and the same virus-specific glycoprotein crucial for induction of the immunological protection against ASF.